A literature review on performance measures of logistics management: an intellectual capital perspective - Ratapol Wudhikarn (2018)
© 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group. Today, logistics management requires a comprehensive set of performance indicators that measure both tangible assets and intellectual capital (IC) of organisations. Nevertheless, most of the measures used in the past mainly related to the financial aspect, although some specific components of IC, such as process efficiency and effectiveness, have been considered. Logistics literature lacks a comprehensive consideration of the diverse IC measures, and it is unclear which area of IC requires more focus and development. Therefore, to explore and identify an opportunity for improvement, this study reviews the academic literature related to IC measures in logistics management. This literature review considers 111 academic articles published between 1994 and 2016. Following the six dimensions of the IC-Index, all indicators obtained from the literature are classified according to IC elements. The key contribution of this review is that it addresses the following gaps in the literature: the limited adoption of comprehensive IC methods in logistics studies; underdevelopment of specific indicators and measures used; failure to consider all human capital as well as renewal and development elements; and, finally, lack of academic research considering the influences among the different IC elements and logistics and financial performance.